1995
DOI: 10.1007/bf02413021
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes in production and nutrient content ofCynodon dactylon (L.) Pers. subjected to water deficits

Abstract: Seasonal changes in water relations, production and mineral composition were studied in a sward of Cynodon dac~lon (L). Pers. subjected to water deficits during a dry summer, and at recovery in autumn. The experiment was carried out under Mediterranean field conditions. Water deficits during summer reduced total dry matter production by 60%, but in autumn there were no differences between treatments. Compared to well-watered sward, the sward grown under drought showed an increase in potassium, calcium and nitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 14 publications
2
17
0
1
Order By: Relevance
“…Calcium, on the other hand, has a prominent role in maintaining cell structure (McLaughlin and Wimmer, 1999) and recovery after a period of water stress (Palta, 1990). Increase of Ca under water deficit has been reported by others (Utrillas et al, 1995;Patakas et al, 2002).…”
Section: Effect Of Water Treatmentsupporting
confidence: 62%
See 2 more Smart Citations
“…Calcium, on the other hand, has a prominent role in maintaining cell structure (McLaughlin and Wimmer, 1999) and recovery after a period of water stress (Palta, 1990). Increase of Ca under water deficit has been reported by others (Utrillas et al, 1995;Patakas et al, 2002).…”
Section: Effect Of Water Treatmentsupporting
confidence: 62%
“…In compliance with this result, Kostopoulou et al (2010) in their study found that stomatal conductance of M. officinalis under similar experimental conditions was not affected by water deficit. On the other hand, little information is available on the effect of water stress on Na and Mg. A decrease in sodium content of Cynodon dactylon was also observed under water deficit conditions (Utrillas et al, 1995). On the contrary, plants of Sorghum bicolor grown on different irrigation regimes did not differ in the concentration of Na (Asgharipour and Heidari, 2011).…”
Section: Effect Of Water Treatmentmentioning
confidence: 87%
See 1 more Smart Citation
“…Although the investigated species have different preferences for water availability (Grime et al 1988;Iwatsuki et al 1995;Utrillas et al 1995), in this study homogeneous water supply increased the biomass of all four species. Therefore, growth increments when the water supply has a homogeneous temporal pattern are a general trend in a large variety of herbaceous species (see also Fay et al 2003;Saeed and El-Nadi 1998;Sepaskhah and KamgarHaghighi 1997).…”
Section: Discussionmentioning
confidence: 81%
“…; and one legume, Trifolium repens L. All of these species are broadly distributed, and they can all grow in a common environment, despite their different water demands. Cynodon dactylon is a C4 plant that is tolerant of high temperatures and low water availability (Utrillas et al 1995). Lolium perenne is common in moist environments and less frequent in dry habitats, and T. repens is common in meadows and pastures and can be found even in dryland (Grime et al 1988).…”
Section: Introductionmentioning
confidence: 99%